Design and Machining Control via Interoperable Function and STEP-NC Data Model - Minhat, Mohamad (2012)

(untitled)
This paper is to propose architecture ofcontroller via Function Block Development Kit (FBDK). It can be used to create an open CNC architecture on ISO 14649 and Function Block (JEC 61499). This offers interoperability, portability, andadaptability. Theproposedframework consists ofthree main modules: (1) STEP-NClnterface, (2) Simulator, and (3) Communication. In order to optimise, the controller should incorporate with various technology related to intelligent, such as kernel software, open communication port and open hardware design. The system will be implemented in CNC controller on actual milling machine. It will simplfy the design of CNC machine controller with the architecture layers responsible for data processing, data storage, execution and f eedback. This paper discusses towards the requirements for global interoperable manufacturing for real-flfe machining system with the architecture layers responsiblefor data processing, data storage, and execution.